2018
DOI: 10.24138/jcomss.v14i4.602
|View full text |Cite
|
Sign up to set email alerts
|

A Recommendation System for Shared-Use Mobility Service through Data Extracted from Online Social Networks

Abstract: In recent years, the shared mobility service has increased in many countries across the world because its low cost and several shared-use mobility applications on mobile devices [1]. Commonly, if a ride is shared between people with similar preferences, users likely feel both more comfortable and safe. In this context, the main goal of this article is to classify users with similar preferences, in automatic manner, to improve user's quality of experience in ridesharing service. To obtain initial data, subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The existing literature advocating the use of ML techniques for SMS providers spans various sharing schemes, including dockless systems [82,83,85,86] and hybrid models encompassing both docked and dockless systems [44,84]. These studies encompass a range of SMS types, from ride-hailing and car-sharing to bike and e-scooter sharing.…”
Section: A User Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature advocating the use of ML techniques for SMS providers spans various sharing schemes, including dockless systems [82,83,85,86] and hybrid models encompassing both docked and dockless systems [44,84]. These studies encompass a range of SMS types, from ride-hailing and car-sharing to bike and e-scooter sharing.…”
Section: A User Analysismentioning
confidence: 99%
“…From our review, methodologies like sentiment analysis, topic modeling, and classification algorithms have been em- Scooter Dockless Survey Generalized Linear Models [86] ployed to dissect data from diverse sources, including social media, surveys, and online news platforms. For instance, [83] introduces a framework to profile ride-sharing users, aiming to enhance service quality by matching users with similar interests. [82] delves into user sentiments about ridehailing services, pinpointing areas like customer satisfaction.…”
Section: A User Analysismentioning
confidence: 99%
“…The new definition covers systems recommending any objects in social media domains such as items, tags, links, people, and communities [17,57]. It has been shown that social considerations improve recommender systems since there is a significant overlap between users' interest and connections [48,56,61].…”
Section: Recommender Systemsmentioning
confidence: 99%
“…Velocity and position of each particle are updated with population law locally in pbest and globally gbest. Velocity and position update formulas are given in (19) and (20), respectively [28]. Acceleration factors wc Inertia weight factor rand(1) Random number in between 0 to 1 rand(2) Random number in between 0 to 1 pbesti,j i th particle best position at iteration k (local) gbestj swarm particle best position until iteration k (Global)…”
Section: ) Modified Particle Swarm Optimization (M-pso)mentioning
confidence: 99%
“…But it has been found that NN is prone to local convergence, slow learner, and overfitting problems in some applications [16]. Recently, support vector machine (SVM) has emerged as a tool to overcome the drawbacks of NN [11], [18], [19]. The SVM has three independent factors that affect its performance significantly.…”
Section: Introductionmentioning
confidence: 99%